C.E. Credit. Kabuki Syndrome and Its Oral Manifestations: A Case Report - Amanda A. Marques; Sabrina R. Ribeiro; Sabrina de C. Brasil; Flávio R. F. Alves (Taylor & Francis Group, 2023)
ABSTRACTBackground Kabuki Syndrome is a rare genetic alteration of autosomal origin, known for five characteristics called Niikawa's Pentad: skeletal abnormalities, short stature, mild to moderate intellectual and developmental disabilities, facial dysmorphism, dermatoglyphic alterations, and postnatal growth deficiency.Case description The present report aimed to highlight the main oral manifestations of Kabuki Syndrome in a nine-year-old patient, emphasizing the importance of a correct diagnosis and multidisciplinary care.Continuing Education Credit Available The practice worksheet is available online in the supplementary material tab for this article. A CDA Continuing Education quiz is online for this article: https://www.cdapresents360.com/learn/catalog/view/20.